1995
DOI: 10.1002/j.2161-0045.1995.tb00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Work Values Similarities Among Students From Six Countries

Abstract: This study examined high school students' selected work values in six countries. The data were analyzed for between-country correlation. Also, the data were analyzed with sex as a variable. The findings indicated selected work values were more similar than dissimilar across countries and cultures. Gender specific results suggested a higher degree of transnational agreement among girls than among their male peers.For the past 35 years behavioral scientists have studied how work values and occupational choice re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
0
12
1
Order By: Relevance
“…However, the literature regarding occupational values of cultural groups is mixed, probably because level of acculturation is not typically an independent variable in the studies that have been conducted. For example, Lebo, Harrington, and Tillman (1995) studied the work values of high school students from six countries and concluded that the values of the groups studied were more similar than different. Because all students studied were from countries with Eurocentric cultural orientations, this finding is not surprising.…”
Section: Because Of Differing Values Systems Men and Women And Peoplmentioning
confidence: 99%
“…However, the literature regarding occupational values of cultural groups is mixed, probably because level of acculturation is not typically an independent variable in the studies that have been conducted. For example, Lebo, Harrington, and Tillman (1995) studied the work values of high school students from six countries and concluded that the values of the groups studied were more similar than different. Because all students studied were from countries with Eurocentric cultural orientations, this finding is not surprising.…”
Section: Because Of Differing Values Systems Men and Women And Peoplmentioning
confidence: 99%
“…(Super 1957: 29) These so-called work values or preferences have been widely explored (Super and Bohn 1973;Dawis and Lofquist 1984;Pryor 1979), and previous research among students has found a strong relationship between an individual's work-specific values and their choice of occupation (Zytowski 1970;Dawis and Lofquist 1984;Lebo et al, 1995). Work values are basically fundamental orientations to worklife which organise and direct attitudes and behaviour, not only in the workplace, but also in other arenas of life.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are universal and culture‐specific aspects of work values and their categorization (Lebo, Harrington, & Tillman, ). People from diverse cultures and speakers of various languages may recognize different work values and divide them into different categories (Schwarzer, Schmitz, & Tang, ).…”
mentioning
confidence: 99%